The History of Manchuria 1840-1948 : a Sino-Russo-Japanese triangle - Nish, Ian (Renaissance Books, 2016)
In A History of Manchuria, Ian Nish describes the turbulent times which the three Northeastern Provinces of China experienced in the last two centuries. The site of three serious wars in 1894, 1904 and 1919, the territory rarely enjoyed peace though its economy progressed because of the building of arterial railways.